Synchronisation of Constitutional Philosophy and the Challenges of Globalization - Yunus, Nur Rohim (ADALAH, 2023)
The essay Synchronising Constitutional Philosophy and the Challenges of Globalisation discusses how the constitution, as the highest legal document, must adapt to global dynamics without losing the fundamental values of a nation. Globalisation brings universal values such as democracy, human rights, and the supremacy of law that often clash with traditional values and local wisdom. In this context, constitutional philosophy plays a role as a foundation in determining legal principles that remain relevant amidst global change. This essay outlines the various challenges faced by the constitution in facing globalisation, including the harmonisation of national law with international standards and the dilemma between openness to change and preservation of national identity. To achieve this balance, this essay proposes a selective and contextual approach in adopting global values, strengthening civic education, encouraging intercultural dialogue, and strengthening the role of constitutional institutions. With the right approach, the constitution is expected to remain the central pillar in maintaining the stability and sovereignty of the state amidst the flow of globalisation. This essay emphasises that the synchronisation between constitutional philosophy and the challenges of globalisation must be carried out carefully to not sacrifice the nation's identity.